Are lapsed donors willing to resume blood donation, and what determines their motivation to do so? - Van Dongen, A.; Abraham, Samuel; Ruiter, R.; Schaalma, H.; De Kort, W.; Dijkstra, J.; Veldhuizen, I. (Wiley-Blackwell, 2012)
BACKGROUND: This study investigated the possibility of rerecruiting lapsed blood donors. Reasons for donation cessation, motivation to restart donation, and modifiable components of donation motivation were examined. We distinguished between lapsed donors who had passively withdrawn by merely not responding to donation invitations and donors who had contacted the blood bank to actively withdraw. STUDY DESIGN AND METHODS: A cross-sectional survey was sent to 400 actively lapsed donors and to 400 passively lapsed donors, measuring intention to restart donation and psychological correlates of restart intention. The data were analyzed using multiple regression analyses. RESULTS: The response rate among actively lapsed donors was higher than among passively lapsed donors (37% vs. 25%). Actively lapsed donors typically ceased donating because of physical reactions, while passively lapsed donors quit because of a busy lifestyle. Nonetheless, 51% of actively lapsed responders and 80% of passively lapsed responders were willing to restart donations. Multiple regression analysis showed that, for passively lapsed donors, cognitive attitude was the strongest correlate of intention to donate in the future (ß = 0.605, p < 0.001), with affective attitude (ß = 0.239, p < 0.05) and self-efficacy (ß = 0.266, p < 0.001) explaining useful proportions of the variance as well. For actively lapsed donors, cognitive attitude was also the strongest correlate of intention (ß = 0.601, p < 0.001), with affective attitude (ß = 0.345, p < 0.001) and moral norm (ß = -0.118, p < 0.05) explaining smaller proportions of the variance. CONCLUSION: The majority of lapsed donors indicated a moderate to high intention to restart donations. Interventions focusing on boosting cognitive and affective attitudes and self-efficacy could further raise such intentions.